Ethanol production from N-acetyl-d-glucosamine by Scheffersomyces stipitis strains - Inokuma, Kentaro (AMB Express, 2016)
N-acetyl-d-glucosamine (GlcNAc) is the building block of chitin, which is one of the most abundant renewable resources in nature after cellulose. Therefore, a microorganism that can utilize GlcNAc is necessary for chitin-based biorefinery. In this study, we report on the screening and characterization of yeast strains for bioethanol production from GlcNAc. We demonstrate that Scheffersomyces (Pichia) stipitis strains can use GlcNAc as the sole carbon source and produce ethanol. S. stipitis NBRC1687, 10007, and 10063 strains consumed most of the 50 g/L GlcNAc provided, and produced 14.5 ± 0.6, 15.0 ± 0.3, and 16.4 ± 0.3 g/L of ethanol after anaerobic fermentation at 30 °C for 96 h. The ethanol yields of these strains were approximately 81, 75, and 82 % (mol ethanol/mol GlcNAc consumed), respectively. Moreover, S. stipitis NBRC10063 maintained high GlcNAc-utilizing capacity at 35 °C, and produced 12.6 ± 0.7 g/L of ethanol after 96 h. This strain also achieved the highest ethanol titer (23.3 ± 1.0 g/L) from 100 g/L GlcNAc. To our knowledge, this is the first report on ethanol production via fermentation of GlcNAc by naturally occurring yeast strains.